(untitled) (African Journal of Biomedical Research, 2020)
This study compared the anaesthetic indices and vital parameters of dogs given propofol with varying analgesic combinations. Nine dogs assigned into three groups were administered Propofol 8mg (IV) combined with Diclofenac 2mg/kg IM -DP group; Tramadol 5mg/kg IM- TP group and Diclofenac 2mg/kg + Tramadol 5mg/kg IM-DTP group. Heart and respiratory rates, temperature and selected anaesthetic indices were determined over a 40-minute period. Onset and duration of analgesia were statistically significant (p<0.05) among groups. Onset of analgesia was D-T-P < T-P < D-P. Duration of analgesia was longest in the T-P group and shortest in D-P group. The duration of anaesthesia was statistically significant (p<0.05) among groups, however onset of drug action was not (p>0.05). In conclusion, the three analgesic-propofol combinations produced anaesthesia of moderate duration. However, the T-P and D-T-P had better outcome based on their faster onset and longer duration of analgesia